(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Obtaining and investigation of compositions with improved performance properties based on SKI-3 rubber is devoted to obtaining rubber based on SKI-3 grade rubber with improved physical-mechanical properties. For carrying out this work, for modification of SKI-3 rubber, butadiene-nitrile rubber of BNK-18 grade and polymethyl methacrylate (PMMA) were used. At the same time model rubber mixtures based on the optimal formulation were prepared. Based on the study of properties of model rubber mixtures of non-crystallizing special-purpose rubber BNK-18 and crystallizing general-purpose rubber SKI-3 it was established that in the composition of formulations of industrial elastomer compositions it is most expedient to use mechanically activated material in a planetary mill for 3 min To study the rheological properties of binary systems SKI-3 + BNK-18 compositions were prepared on rolls at a temperature of 140°C during 15 minutes and the obtained single-phase compositions under different loads and temperatures (from 130 to 173°C) had the melt flow indices of this composition determined. Thus as a result the technology of processing rubber mixtures based on SKI-3 + BNK-18 was determined; namely; processing temperature 175°C and pressure 12 MPa. On the basis of SKI-3 + BNK-18 rubber mixtures were prepared and vulcanization parameters were determined; vulcanization time 23 min and temperature 160°C. Study of physical-mechanical properties of vulcanizates showed that the tensile strength of the obtained rubber is 23 MPa, these indicators are 1.6 times greater than the standard.